2021
DOI: 10.3390/jcm10204688
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences among Sardinians with Alcohol Use Disorder

Abstract: Sardinia is an Italian island in the Mediterranean characterized by secular isolation and the singular genetic characteristics of its inhabitants. Findings obtained in populations with diverse genetic make-up and cultural background indicate gender differences and/or similarities in drinking characteristics of patients with alcohol use disorder (AUD). Knowledge of these characteristics in AUD patients is useful to improve access to treatments. This paper investigated the drinking characteristics of 66 female a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…We identified nine meta‐analyses where the authors reported that they conducted formal subgroup analyses (Table 1, Table S3; Agabio et al., 2023; Agabio, Baldwin, et al., 2021; Agosti et al., 2012; Donoghue et al., 2015; Feinn & Kranzler, 2005; Hartwell et al., 2020; Lejoyeux & Lehert, 2011; Mason & Lehert, 2012; Pierce et al., 2018), of which three compared acamprosate to placebo for AUD (Lejoyeux & Lehert, 2011) or AD (Donoghue et al., 2015; Mason & Lehert, 2012), and four compared naltrexone to placebo for AD (Agosti et al., 2012; Donoghue et al., 2015; Feinn & Kranzler, 2005; Hartwell et al., 2020), and three compared baclofen to placebo for AD (Pierce et al., 2018) or AUD (Agabio et al., 2023; Agabio, Pisanu, et al., 2021). Across 61 individual subgroup analyses reported in these nine meta‐analyses (median [IQR] 6 [2, 8] per meta‐analysis), 33 (54%) were based on baseline participant‐level characteristics and 28 (46%) were based on trial‐level characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…We identified nine meta‐analyses where the authors reported that they conducted formal subgroup analyses (Table 1, Table S3; Agabio et al., 2023; Agabio, Baldwin, et al., 2021; Agosti et al., 2012; Donoghue et al., 2015; Feinn & Kranzler, 2005; Hartwell et al., 2020; Lejoyeux & Lehert, 2011; Mason & Lehert, 2012; Pierce et al., 2018), of which three compared acamprosate to placebo for AUD (Lejoyeux & Lehert, 2011) or AD (Donoghue et al., 2015; Mason & Lehert, 2012), and four compared naltrexone to placebo for AD (Agosti et al., 2012; Donoghue et al., 2015; Feinn & Kranzler, 2005; Hartwell et al., 2020), and three compared baclofen to placebo for AD (Pierce et al., 2018) or AUD (Agabio et al., 2023; Agabio, Pisanu, et al., 2021). Across 61 individual subgroup analyses reported in these nine meta‐analyses (median [IQR] 6 [2, 8] per meta‐analysis), 33 (54%) were based on baseline participant‐level characteristics and 28 (46%) were based on trial‐level characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Agabio et al. found that women were older than men at the age of first drink, regular drinking, and onset of AUD, and progressed faster than men from regular use to AUD onset ( 68 ). More importantly, the sex difference occurs in BDNF SNP reported by alcohol-related studies.…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, 12-month prevalence of alcohol dependence corresponded to 3.4% of the general population, and 5.2% and 1.7% of male and female populations, respectively (Rehm 2015). However, the gender gap in AUD is narrowing, particularly in the younger population (Agabio 2021;Slade 2016).…”
Section: B a C K G R O U N D Description Of The Condition Prevalence ...mentioning
confidence: 99%